Fight Club - Павлович, Тетяна Іванівна (My University, 2026)
Chuck Palahniuk’s Fight Club is a gritty exploration of masculinity, nihilism, and the crushing weight of consumerist culture. At its core, it is a psychological battle between the 'Everyman' who follows society's rules and the 'Anarchist' who wants to burn them down. Each character represents a different response to a world that feels increasingly hollow and ephemeral.
Home Reading
Keywords: Home Reading